(untitled) (Law and world, 2018)
The article reviews main criminological theories and their importance in the prevention of crime, ideas of classical school of criminology and criminal law, criminal anthropology and sociological school in relation to criminality and the cause of crime and prevention. Main directions around the issue are analyzed.Without the science of criminology it is impossible to study the crime in the state and prevent it and improve legislative activities. Criminological expertise of draft laws is of utmost importance to conduct legislative activities without the use of criminological knowledge and it can’t be determined what concrete law, especially, criminal and administrative laws, can be prevented, suppressed, or otherwise provoked by criminal conduct in the future. It is important for the study of complex causes of crimes of criminology and prevention of crime, planning and predicting the crime. Without criminological studies, investigations and rehabilitation of victims of crime can not be re-socialized and, most importantly, legal culture in society can not be increased. Thus, one of the tasks of modern criminology should be to develop criminology and scientifi c research at the legal faculties of higher education institutions.